Demystifying the Cost of Serverless Computing: Towards a Win-Win Deal - Liu, Fangming; Niu, Yipei (IEEE transactions on parallel and distributed systems, 2024)
Serverless is an emerging computing paradigm that greatly simplifies the development, deployment, and maintenance of cloud applications. However, due to potential cost issues brought by the widely adopted pricing, it is difficult to answer how to use and operate serverless computing services from the perspectives of users and providers. To demystify the cost of serverless computing, we present one of the first studies that develops an analytical model for serverless cost from the perspectives of users and providers, by comparing it to Infrastructure-as-a-Service. Based on the model, driven by real-world traces, extensive simulation results verify the following cost issues: 1) For the users, serverless is not always cost-saving, even possibly leading to expense explosion; 2) The serverless providers are in urgent need of widening use scenarios to improve resource utilization and raise revenue; 3) The prevailing pricing fails to neither reduce the risk of expense explosion nor meet the need of attracting more workloads. To remove the cost barrier, we propose future function , auction-based pricing for serverless, to offer discounts to the users as well as boost profit for the providers. Experimental results show the duration price of functions can be reduced by 57.5% on average for 13.5% of users yet without harming the revenue of providers.